Gut to brain: essential micronutrient and trace element manganese transport, function and toxicity - Zou, Jiaqi; Yerramilli, Riya; Aydemir, Tolunay Beker (Frontiers in Physiology, 2025)
This review provides a comprehensive analysis of manganese (Mn) metabolism and its regulatory roles across multiple biological levels. By examining Mn homeostasis mechanisms, including Mn absorption, excretion, distribution, and transport across the intestines, liver, and brain, this work highlights the integrative nature of Mn physiology. Additionally, it explores routes of Mn overexposure and the consequences of Mn dysregulation on various organ systems, with a focus on neurotoxicity, as well as the genetic and environmental factors that contribute to Mn homeostasis. This review synthesizes insights into metal transporters to advance our understanding of their roles in maintaining systemic and brain Mn homeostasis under healthy conditions and their contribution to Mn dysregulation in disease states, particularly neurological disorders. By focusing on Mn transport and regulation across multiple physiological systems and its impact on health and disease, we aim to bridge the gap between molecular-level processes and whole-body physiology.